Determination of proteins to obtain an adhesive material at different times and temperatures, from the wet blue chip of the leather tanning process by means of alkaline hydrolysis - Miguel Valdez-Urbina (2019)
The main objective of the present study was to investigate the production of an adhesive material from the wet blue chip produced from the leather tanning process. Dry blue wet chip in an amount of 25 gr was subjected to alkaline hydrolysis with 0.3N, 0.4N and 0.5N of NaOH, the hydrolysis was carried out at temperatures of 50 ° C, 60 ° C and 70 ° C, It took 3 hours and 4 hours to stop the hydrolysis of the chip, by neutralizing it with H2SO4 until reaching a pH range between 7 and 8. In the characterization of the wet blue chip, 45.84% of protein was present, being mostly Collagen and 23.21 mg / kg of chromium with a 50.42% moisture content. The highest concentration of proteins obtained from the hydrolysis process was at the conditions of 60 ° C of temperature, 0.4N of NaOH and 4 hours for neutralization, with an average of 9.32 mg / mL of protein, presenting highly significant differences ( p <0.01) with the other treatments. The concentration of proteins obtained from the optimal hydrolysis conditions, would indicate an adhesive material that could be used in different applications, since the concentration of collagen in skins is greater than 30% and in chip exceeds 39% of the composition.